Exploring the relationships between gender, affective and cognitive empathy, and aggressive behaviour in young Western Cape children - Mayosvi, Panashe Agatha (Department of Psychology, 2019)
Aggression among children and adolescents has been a major area of focus for many researchers across the world. In South Africa, specifically, aggressive behaviour has increasingly become problematic. Aggression can be regarded as antisocial or offending behaviour. Aggressive behaviour usually results in unfavorable consequences for both the victim and the assaulter. Although aggression usually manifests itself physically, it also has underpinning psychological factors. One of the factors that most research has looked at in relation to aggressive behaviour is empathy. Most studies have, however not looked at how the different components of empathy separately affect or predict aggressive behaviour. Females have generally been found to be more empathic and less aggressive; however the relationships between the variables have not been adequately simultaneously investigated. This project therefore assessed the effect of both affective empathy and cognitive empathy on the manifestation of aggressive behaviour in young Western Cape children. The study focused specifically on externalized aggressive behaviour. The study further aimed to investigate if the association between these two components of empathy and externalized aggressive behaviour differed across gender. The study made use of quantitative measures to examine the relationships between the above-mentioned variables. The study recruited a total of 249 Colored, English speaking learners aged 3 to 12 and their parent or caregiver. The sample had approximately equivalent numbers of boys and girls and an approximately equal number of children from low, middle and high SES to ensure that each demographic stratum was represented sufficiently. Statistical analyses of the data indicated that in general the children in the sample had low levels of aggressive behaviour. No statistically significant gender difference in aggression was found. A non-significant relationship was found between affective empathy and aggressive behaviour. A significant negative relationship was however found between cognitive empathy and aggressive behaviour. The correlation between cognitive empathy and aggressive behaviour was significantly evident only among boys; boys who scored low in cognitive empathy scored high on the externalized subscale of CBCL. The study also investigated the effect of potential covariates, Age, SES and IQ on aggressive behaviour; none of these covariates seemed to influence aggressive behaviour. The results of this study provide vital inferences regarding prevention of aggressive behaviour in children. There were however some disparities from what literature reports and that require further exploration. Keywords: affective empathy, cognitive empathy, externalized aggressive behaviour, gender